ABBREVIATIONS IN THE ENGLISH AND UZBEK LANGUAGES: FORMATION MECHANISMS, STYLISTIC LOAD, AND COMMUNICATIVE EFFECTIVENESS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article explores abbreviations in the English and Uzbek languages with a focus on their formation mechanisms, stylistic load, and communicative effectiveness in modern discourse. The study employs a comparative linguistic approach to analyze structural types of abbreviations, including initialisms, acronyms, and clipped forms, as well as their functional roles across scientific, official, media, and digital communication. Special attention is given to the contribution of abbreviations to linguistic economy, information compression, and stylistic expressiveness. The findings provide theoretical and practical insights for functional stylistics, contrastive linguistics, and translation studies.